Comparison of infant feeding practices in two health sub-districts with different baby friendly status in Mpumalanga province - Van der Merwe, Susara Maria (Stellenbosch : Stellenbosch University, 2012)
Thesis (MNutr)--Stellenbosch University, 2012.